2017
DOI: 10.18276/cej.2017.2-05
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Coach-Athlete Working Alliance on Affect and Burnout Among High Level Coaches

Abstract: Research suggests that the numbers of coaches who are suffering from burnout symptoms are considerably high among coaches in elite sport. In this study, the authors explore the effects of the coach-athlete working alliance on positive-and negative affect and burnout in a group of high-level coaches. An online survey, consisting of the Working Alliance Inventory-Short Version, the Positive and Negative Affect Schedule and the Maslach Burnout Inventory, was completed by a sample of 299 coaches working with elite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…The first objective of this study was to determine whether the three dimensions of working alliance (i.e., Bond, Tasks and Goals) represent the factorial structure of working alliance in a coaching setting, using the Dutch translation of the measure WAI-S. By applying a standard CFA-framework that sequentially employed the testing of one-, two-, and three-factor structures of working alliance throughout sessions, our main, as well as post hoc findings, indicated that the three-factor model of the WAI-S most adequately represented our data. These results are in line with most research on this topic which delineated a multidimensional structure of the WAI-S (i.e., three factors; [ 12 , 17 19 , 25 ]), which is congruent with Bordin’s [ 7 ] original conceptualization of working alliance. Similar to Hukkelberg and Ogden’s [ 17 ] study results, we found Item 9 (“My coach does not understand what I am trying to accomplish in coaching”—goals factor) and Item 11 (“My coach and I have different ideas on what my problems are"—goals factor) to have relatively weak factor loadings [ 58 , 69 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The first objective of this study was to determine whether the three dimensions of working alliance (i.e., Bond, Tasks and Goals) represent the factorial structure of working alliance in a coaching setting, using the Dutch translation of the measure WAI-S. By applying a standard CFA-framework that sequentially employed the testing of one-, two-, and three-factor structures of working alliance throughout sessions, our main, as well as post hoc findings, indicated that the three-factor model of the WAI-S most adequately represented our data. These results are in line with most research on this topic which delineated a multidimensional structure of the WAI-S (i.e., three factors; [ 12 , 17 19 , 25 ]), which is congruent with Bordin’s [ 7 ] original conceptualization of working alliance. Similar to Hukkelberg and Ogden’s [ 17 ] study results, we found Item 9 (“My coach does not understand what I am trying to accomplish in coaching”—goals factor) and Item 11 (“My coach and I have different ideas on what my problems are"—goals factor) to have relatively weak factor loadings [ 58 , 69 ].…”
Section: Discussionsupporting
confidence: 89%
“…So far, only two studies described the factorial structure of the working alliance in a coaching context, more specifically sports coaching. These particular studies [ 24 , 25 ] used an adjusted version of the WAI-S for sports coaching and found contrasting evidence for either a one- or three-factor structure. However, as the relationship between coaches and athletes represents an intense, asymmetrical power dynamic [ 26 ], the working alliance in sports coaching may deviate from the theoretical conceptualization by Bordin [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The WAI-S has been shown to possess good construct validity [39]. A Norwegian version of the WAI-S, translated and adjusted for the sport context by Moen and Myhre (2017) [21], was used. Examples of items covering the three dimensions of the working alliance are (1) bond—“There is mutual trust between my coach and me,” (2) goal—“My coach and I work on mutually agreed-upon goals,” and (3) task—“My coach and me agree about the steps I need to take to improve in my sport.” The Cronbach’s alpha coefficients of the three subscales were 0.73, 0.92 and 0.90, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The progress of athletic performance is brought about by changes in skills and capacities, and the coach-athlete relationship may, therefore, be considered to be a change-inducing relationship [21]. Based on the work of Bordin (1979), such a relationship is defined as a working alliance between the helper and the help-seeker [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation